Wishypoofs and hiccups - Citro, Asia; Lindsay, Marion (Seattle, WA : The Innovation Press, 2021)
When Pip shows up with a new look that's just as much of a surprise to him as to Zoey and Sassafras, the trio knows something strange is happening in the forest. They retrace Pip's steps only to see another magical friend change right before their eyes! It's up to the team to figure out what is happening and how to change the magical animals back before things get any more serious.
3.3
K-3
Some copies purchased with funds from an OASL Connie Hull Mini-Grant, Mt. View 2024
Keywords: Cats -- Juvenile fiction; Animals, Mythical -- Juvenile fiction; Wishes -- Juvenile fiction; Magic -- Juvenile fiction; Rescue work -- Juvenile fiction; Cats -- Fiction; Animals, Mythical -- Fiction; Wishes -- Fiction; Magic -- Fiction; Rescue work -- Fiction; Fantasy; Fantasy fiction